A Pragmatic Study of Generalized and Particularized Implicatures in “The Arrangers of Marriage” from Adichie’s The Thing Around your Neck - YOKOSSI, Tchorkpa Daniel (My University, 2022)
ABSTRACT This investigation seeks to make sense of Adichie’s “The Arrangers of Marriage”. In fact, as Yule (2010) put it, “ Our understanding of what we read doesn’t come directly from what words and sentences are on the page, but the interpretations we create, in our minds, of what we read”, (p. 151). Following the foregoing quotation, the study scrutinizes conversational implicatures in the above mentioned narrative story to disclose the subtly implied messages therein from a pragmatic angle. The study is premised on the hypothesis that a number of important messages are implied in the short story through both generalized and particularized implicatures out of consideration of the readers’ scripts of the scenes and events presented within, (Mey, 2001: 237). To attain the aim of the investigation, the study appeals to the descriptive qualitative methodology. Via this method, the various scenes and events presented in the narrative are appraised and related interpretations carried out on the basis of their schemata and scripts. The study has made important findings. Among several others, it is uncovered that hasty marriage brings undesirable, irrevocable, unbearable, and deadly consequences to the newly wedded couple. Moreover, marriage shouldn’t be premised on materialism especially as not all that glitters is gold. Indeed, material comfort doesn’t guarantee a couple’s happiness. The change of the key characters’ native Igbo names to English ones in a host country is evocative of their acculturation. Chinaza Agatha Okafor’s refusal to forsake her native language in favor of American English only, is her rejection of self-denial and loss of identity in a foreign country. Furthermore, her resistance to the English name given to her by her new husband, is revelatory of the writer’s feministic trend and her position with regard to cultural alienation. KEYWORDS: Implicature, pragmatics, schema, script, study.
Keywords: KEYWORDS: Implicature; pragmatics; schema; script; study.